Emotion Regulation Among Adolescents With Pediatric Depression As a Function of Anxiety Comorbidity - Dochnal, Roberta; Vetró, Ágnes; Kiss, Enikö; Baji, Ildikó; Lefkovics, Eszter; Bylsma, Lauren M.; Yaroslavsky, Ilya; Rottenberg, Jonathan; Kovacs, Maria; Kapornai, Krisztina (Frontiers in Psychiatry, 2019)
Background: Both depression and anxiety (two of the most common internalizing psychopathology among youths) are associated with difficulties in emotion regulation (ER). Little is known about whether anxiety as a comorbid condition has an effect on the habitual use of different ER strategies in youngsters with depression histories. We aimed (1) to compare ER in adolescents with histories of childhood onset major depression (MDD) with and without comorbid anxiety and (2) to examine whether certain ER response clusters (Cognitive, Social, Behavioral/Physical) characterize comorbid children and adolescents. Methods: We analyzed data on 217 youths (11-18 y.o.) with depression history; 85 subjects with lifetime anxiety comorbidity (comorbid group), 132 without lifetime anxiety (non-comorbid group). Psychiatric diagnosis was established by comprehensive DSM IV based diagnostic procedure. ER strategies were examined via the self-rated “Feelings and Me” Child version questionnaire (FAM-C). Results: The comorbid group used maladaptive ER strategies significantly more frequently than the non-comorbid youngsters. The Behavioral/Physical and Social ER skills, especially items reflecting social withdrawal and self-harm were responsible for the higher maladaptive scores. Limitations: Our study is a cross sectional analysis, thus we have no information about the development or the onset of maladaptive ER strategies. Therefore, we couldn’t examine whether maladaptive ER was a risk factor or a consequence of the internalizing psychopathology and comorbidity. Conclusions: Comorbid anxiety worsens the impaired use of ER strategies in depression prone youth. Further longitudinal research is needed to explore the causal role of dysfunctional ER in the development of internalizing psychopathology.